Blind Detection for 5G MIMO Short-Packet Communication System - Yeh, Bo-Heng; Ueng, Fang-Biau; Li, Yun-Yu (Lecture notes in engineering and computer science, 2021)
-The upcoming fifth-generation (5G) systems will need to support novel traffic types that use short packets. The short-packet communication (SPC) is a concerned application in the subject about low-latency high-reliability. Due to the property of SPC, efficiently reducing the length of cyclic prefix (CP) and length of pilot is an important study. As far as we know, no research has been presented for blind receiver with joint channel shortening, carrier frequency offset (CFO) compensation and data detection for 5G SPC systems. Therefore, we employ the blind system in the receiver which does not need pilot and reduce the length of CP as short as possible. CFO estimation and channel shortening have been addressed individually. However, this leads to a circular set of assumptions, since standard CFO estimators perform poorly when the channel is longer than the guard interval, and standard channel shorteners assume that CFO estimation has already been perfectly performed. This paper proposes a blind receiver for uplink reception of a multi-input multi-output (MIMO) single-carrier interleaved frequency-division multiple-access (SC-IFDMA) system transmitting over a highly-dispersive channel, which is affected by both timing offsets (TOs) and frequency offsets (CFOs). When the length of CP is insufficient to compensate for channel dispersion and TOs, a common strategy is to shorten the channel by means of time-domain equalization, in order to restore CP properties and ease signal reception. This paper proposes a blind receiver for SPC systems that do not need pilot and can solve the interblock interference (IBI) caused by insufficient CP length. The receiver exhibits a four-stage structure: the first stage performs blind shortening of channel impulse responses (CIRs), without needing neither a priori knowledge of the CIRs to be shortened, nor preliminary compensation of the CFOs; the second stage performs joint estimation and compensation of the CFOs; the third stage implements signal-to-noise ratio (SNR) maximization, without requiring knowledge of the shortened CIRs; the fourth stage performs blind detection with fractional lower-order statistics constant modulus algorithm (FLOS-CMA). Some simulation examples are given to show the effectiveness and comparisons of the proposed receiver.